Pelatihan 3D Print FDM Untuk Teaching Factory Di SMK Dian Kirana Sragen - Finali, Asmar; Wahid, Muhammad Abdul (Jurnal Pengabdian kepada Masyarakat UBJ, 2025)
FDM (Fused Deposition Modeling) 3D Printer tool training to support Teaching Factory (TEFA) in SMK aims to improve technical skills and students' readiness to face the challenges of industry 4.0. 3D printing technology has become an important innovation in the manufacturing world, which allows the creation of three-dimensional objects quickly and precisely. Therefore, mastery of this technology is very important for SMK, especially those involved in the TEFA program. This community service activity was carried out to provide practical training to teachers on how to operate an FDM 3D Printer, as well as understand the design and production process using three-dimensional printing technology. The training includes basic theory on how the FDM 3D Printer machine works, CAD programming, and steps in making prototypes and products using 3D printing. Through this training, it is hoped that Dian Kirana Sragen Vocational School can further strengthen the TEFA concept by providing facilities and tools that comply with industry standards. It is hoped that SMK Dian Kirana Sragen teachers can be better prepared to face the increasingly developing industrial world. The training was held through a combination of theory and direct practice methods, with the aim of providing a comprehensive understanding to participants. The results of this activity provide a real contribution to improving the quality of vocational education and strengthening the relationship between the world of education and the world of industry through TEFA products.